2020
DOI: 10.1186/s12960-020-00518-3
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and newborn care during the COVID-19 pandemic in Kenya: re-contextualising the community midwifery model

Abstract: Peripartum deaths remain significantly high in low- and middle-income countries, including Kenya. The COVID-19 pandemic has disrupted essential services, which could lead to an increase in maternal and neonatal mortality and morbidity. Furthermore, the lockdowns, curfews, and increased risk for contracting COVID-19 may affect how women access health facilities. SARS-CoV-2 is a novel coronavirus that requires a community-centred response, not just hospital-based interventions. In this prolonged health crisis, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 36 publications
(46 reference statements)
1
59
0
Order By: Relevance
“…Focusing on PHC is particularly important in the context of Nigeria, being closer-to-the community. Also, PHC and use of lower-cadre health workers has been argued to be the golden goose needed to address care provision during the pandemic [ 36 , 37 ]. Incorporating tailored respectful maternity care [ 38 ] as part of on-going COVID-19 trainings will make a significant difference at all levels, more so for PHC workers.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on PHC is particularly important in the context of Nigeria, being closer-to-the community. Also, PHC and use of lower-cadre health workers has been argued to be the golden goose needed to address care provision during the pandemic [ 36 , 37 ]. Incorporating tailored respectful maternity care [ 38 ] as part of on-going COVID-19 trainings will make a significant difference at all levels, more so for PHC workers.…”
Section: Discussionmentioning
confidence: 99%
“…Although this was the case, it is important to highlight that poor mental health during pregnancy has numerous detrimental effects for both expectant women and the unborn babies [ 17 , 18 ], and it is likely that the pandemic exacerbates the risk for mental illness and sub-optimal perinatal health care [ 15 ]. For instance, there have been reports within the Kenyan context of decreased and delayed antenatal attendance arising from the fear of COVID-19 infection and restricted access to care due to lockdowns and imposed curfew hours that limit access to services within designated hours [ 44 , 45 ]. The implications of these are that some pregnant women who opt to delay seeking care may miss out on the opportunity of early screening for mental health symptoms during routine care [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, there have been reports within the Kenyan context of decreased and delayed antenatal attendance arising from the fear of COVID-19 infection and restricted access to care due to lockdowns and imposed curfew hours that limit access to services within designated hours [ 44 , 45 ]. The implications of these are that some pregnant women who opt to delay seeking care may miss out on the opportunity of early screening for mental health symptoms during routine care [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,[16][17][18][19] For examples, studies in Ethiopia, Kenya, Malawi, and Uganda have reported significant increases in stillbirth rates, neonatal mortality, maternal mortality and decreases in institutional deliveries and quality of care provided. 17,[20][21][22][23] Therefore, objectives of this study were to: (1) determine the impact of the lockdown on maternal and perinatal outcomes at two tertiary hospitals in Harare, Zimbabwe, using a maternal audit, and (2) estimate the potential effect of COVID-19 related decreases in coverage of maternal and newborn health interventions on maternal, neonatal and stillbirth mortality at the national level using the Lives Saved Tool (LiST).…”
mentioning
confidence: 99%